Implementasi Sistem Kontrol dan Monitoring Smart Home Menggunakan Integrasi Protokol Websocket dan MQTT - Nimas Raya Ahsy; Adhitya Bhawiyuga; Dany prima Kartikasari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The Internet of Things is the interconnection of various devices over the internet, allowing these devices to communicate with one another. The diversity of requirements and format of data from devices in IoT might cause problems in the aspect of interoperability. The integration of IoT with Web of Things (WoT) can serve as a solution so that users can access devices in IoT through the same source. One technology that is easier to implement using IoT and WoT is Smart Home (home automation). In Smart Home there are devices like sensors and microcontrollers with limited resources, therefore the MQTT protocol is used as a support for communication. WebSocket, as a WoT protocol, is used as a communication protocol so that the controlling and monitoring system Smart Home can run in real time. To support the system to remain safe in the exchange of data and in the management of devices connected to the system, JSON Web Tokens are also used. Based on the results of implementation and testing, it is evident that the system has a delay of 1 millisecond, while the most optimal response time is when the NodeMCU sends 10 data at a time to a server that only takes 1 second. In addition, LED actuator devices and fans can function properly according to orders obtained from users through a web application.